Enhancing the mirror illusion with transcranial direct current stimulation. (May 2015) - Jax, Steven A.; Rosa-Leyra, Diana L.; Coslett, H. Branch
Abstract: Visual feedback has a strong impact on upper-extremity movement production. One compelling example of this phenomena is the mirror illusion (MI), which has been used as a treatment for post-stroke movement deficits (mirror therapy). Previous research indicates that the MI increases primary motor cortex excitability, and this change in excitability is strongly correlated with the mirror's effects on behavioral performance of neurologically-intact controls. Based on evidence that primary motor cortex excitability can also be increased using transcranial direct current stimulation (tDCS), we tested whether bilateral tDCS to the primary motor cortices (anode right-cathode left and anode left-cathode right) would modify the MI. We measured the MI using a previously-developed task in which participants make reaching movements with the unseen arm behind a mirror while viewing the reflection of the other arm. When an offset in the positions of the two limbs relative to the mirror is introduced, reaching errors of the unseen arm are biased by the reflected arm's position. We found that active tDCS in the anode right-cathode left montage increased the magnitude of the MI relative to sham tDCS and anode left-cathode right tDCS. We take these data as a promising indication that tDCS could improve the effect of mirror therapy in patients with hemiparesis. Highlights: We tested whether bilateral M1 tDCS would modify the mirror illusion. Anode right-cathode left tDCS increased the magnitude of the mirror illusion. Mirror therapy could be improved with tDCS.